Value assessment of NMPA-approved new cancer drugs for solid cancer in China, 2016-2020 - Jing Luo; Shunlong Ou; Hua Wei; Xiaoli Qin; Rui Peng; Song Wang; Qian Jiang (Frontiers Media S.A., 2023)
BackgroundWhether the high cost of cancer drugs is commensurate with their value to patients, which has become the focus of public concern. We aimed to assess the value of new cancer drugs approved for solid cancer in China and to explore the association between price and value of drugs.MethodsWe identified all new drugs for solid tumor that approved by the China's National Medical Products Administration (NMPA) between 2016 and 2020. The value of these drugs was assessed according to the American Society of Clinical Oncology Value Framework (ASCO-VF) and the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). We calculated Cohen's κ statistic to describe agreement between the two frameworks. Spearman's correlation coefficient was used to evaluate the correlation between price and value of drugs.ResultsBetween 2016 and 2020, 37 new drugs were approved by the NMPA for solid tumor and we could evaluate the value of 28 drugs (76%). Eight (29%) of drugs were approved for non-small-cell lung cancer and 6 (21%) for breast cancer. ASCO-VF scores had a range of −20 to 110.1, and the median score was 43.3 (inter-quartile range 27.1-58.35). Only seven drugs (25%) met the ASCO-VF cutoff score. By the ESMO-MCBS, 13 drugs showed a meaningful value. Agreement between these two frameworks thresholds was only fair (κ = 0.515, P < 0.05). We found no statistically significant correlation between launch price of drugs and clinical benefit according to both frameworks.ConclusionsNot all NMPA-approved new cancer drugs had meaningful value as measured by ASCO-VF or ESMO-MCBS. There was no significant correlation between drug price and the level of clinical benefit.